Guideline of Learning Summary Writing Activities for Students in Basic Educational - Wongchai, Sanga; Pumpachart , Thanachaporn (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This article aimed to guideline of learning summary writing activities for students in basic educational. The National Educational Testing Institute (Public Organization) conducts examinations to assess the quality of learners’ summary writing ability in Thai language subjects using a written subject test. Developing summary writing ability is a mission for teachers, who must design learning activities to enhance students’ summary writing ability effectively. The learning activities for summary writing based on the survey, question, read, write strategy consist of four steps: searching for resources, questioning, reading comprehension and summary writing. learning Design for summary writing activities based on the SQRW strategy will help the main ideas from text reading, organize the content coherently, choose words that accurately convey meaning, construct complete sentences, communicate clearly, spell correctly, and use punctuation and spacing appropriately.